Flight Behavior of Individual Aerial Insectivores Revealed by Novel Altitudinal Dataloggers - Dreelin, R. Andrew; Shipley, J. Ryan; Winkler, David W. (Frontiers in Ecology and Evolution, 2018)
Swallows and martins (Aves: Hirundinidae) are well-studied with respect to their breeding biology, but major aspects of their individual aerial movement behavior and ecology are relatively poorly documented. We deployed a novel tag technology, an altitude datalogger, on breeding populations of Purple Martin (Progne subis), Tree Swallow (Tachycineta bicolor), and Barn Swallow (Hirundo rustica) in upstate New York during the summer of 2016, providing individual-level flight data on a per minute basis. Using mixed models, we investigated differences in flight altitudes across species and varying atmospheric conditions. The major findings were: 1) three species spent significantly different proportions of their time in distinct aerial strata despite extensive behavioral plasticity, 2) individuals of each species responded differently to atmospheric conditions depending on the time of day and their altitude, and 3) the species differed from one another in the relationships between their flight altitudes and weather variables, suggesting different strategies for tracking their environment and/or prey. More research is needed to accurately determine the relationships between specific meteorological variables and altitude. We encourage broader use of this methodology to better understand the behavior and ecology of aerial insectivores globally.